The Relationship of Knowledge, Attitude, and Mother Action About the Implementation of Early Breastfeeding Initiation - Titi Saparina; Rismah (MIRACLE Journal Of Public Health, 2021)
Based on a preliminary study conducted at the Anggalomoare Public Health Center, it shows that Antenatal Care (ANC) visits for third trimester pregnant women averaged 35 per month. The target achieved was only 62,5% of the target of 85%. The purpose of this study was to determine the relationship between the level of knowledge, attitudes and actions of mothers regarding the implementation of early breastfeeding initiation at Anggalomoare Public Health Center.This research is a survey research with a cross-sectional Study approach. The population of this study is the total number of pregnant women whose expected day of birth is in February, totaling 32 people. The sampling method was simple total population. The method of analysis used statistical tests, namely the chi square test and the Phi test.The results of this study indicate that there is a strong relationship between maternal knowledge and the implementation of early breastfeeding initiation (ρ-value=0,000; phi=0,674), there is a moderate relationship between maternal attitude and implementation of early breastfeeding initiation (ρ-value=0,002; phi=0,592), there is a strong enough relationship between maternal actions and implementation early initiation of breastfeeding (ρ-value=0,033; phi=0,516) at the Anggalomoare Health Center, Konawe Regency. It is hoped that the Puskesmas will always provide information for breastfeeding mothers and pregnant women about the importance of implementing early breastfeeding initiation. Information can be given through counseling to mothers during pregnancy, postpartum and while breastfeeding their children.